Indoor Built Environment and Older Adults' Activity: A Systematic Review. Issue 2 (18th June 2023) - Azim, Farah T.; Ariza-Vega, Patrocinio; Gardiner, Paul A.; Ashe, Maureen C.
Abstract: Although the physical environment can influence people's activity, there are few knowledge syntheses for indoor environments and older adults' daily life routines. Therefore, we conducted a systematic review of peer-reviewed evidence to inform future research and practice. Inclusion criteria were studies with any research designs, across all years and languages focused on older adults 60 years of age or more, on physical activity/sedentary behaviour and the indoor environment. After searching five databases, two authors completed title/abstract and full-text screening. The last search was on December 19, 2020. We screened 1, 367 citations, and included 23 studies situated in private or collective dwellings (e.g., assisted living). We identified physical activity-supportive indoor features across three domains: campus (e.g., amenities, pathways), building (e.g., area, floor level), and fixtures (e.g., elevators, hallways). Knowledge of indoor environmental factors for older adults' engagement in daily activities can guide future research and policy on housing design.